2006
DOI: 10.2460/ajvr.67.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on cranial migration of epidurally injected methylene blue in recumbent dogs

Abstract: Body positioning and amount of recumbency time influence cranial migration of epidurally injected methylene blue. If greater cranial migration of an epidurally administered drug is desired, placing the patient in lateral recumbency with the surgical site on the dependent side may precede surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…It has been recommended that dogs be positioned in sternal recumbency and kept in this position following injection to provide bilateral analgesia or in lateral recumbency with the surgical site as the dependent side until the block has taken effect (32). One study using canine cadavers showed that if greater cranial migration of an epidurally administered drug is desired, placing the patient in lateral recumbency with the surgical site on the dependent side for 30–40 min may precede surgery (gravity effect) (32).…”
Section: Local Anestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recommended that dogs be positioned in sternal recumbency and kept in this position following injection to provide bilateral analgesia or in lateral recumbency with the surgical site as the dependent side until the block has taken effect (32). One study using canine cadavers showed that if greater cranial migration of an epidurally administered drug is desired, placing the patient in lateral recumbency with the surgical site on the dependent side for 30–40 min may precede surgery (gravity effect) (32).…”
Section: Local Anestheticsmentioning
confidence: 99%
“…One study using canine cadavers showed that if greater cranial migration of an epidurally administered drug is desired, placing the patient in lateral recumbency with the surgical site on the dependent side for 30–40 min may precede surgery (gravity effect) (32). In the authors’ experience, placing the affected limb in a dependent position for the duration of the clipping and surgical preparation (approximately 30 min) is enough time to achieve this effect without delaying surgery.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Johnson et al 1996 o utilizaram por se dissolver facilmente em solução fisiológica, possibilitando e facilitando a injeção no espaço peridural e pela mancha produzida ser de fácil visualização e mensuração. Gorgi et al 2006 utilizaram azul de metileno no espaço peridural de cães eutanasiados para avaliar o efeito do decúbito em sua distribuição.…”
Section: Introductionunclassified
“…The site of action of local analgesics given epidurally is controversial, but the sensory and motor blockade is attributed to the direct contact with the superficial layers of the nerve roots in the spinal cord [6], [7]. The migration of drugs within the epidural space can be influenced by different factors, including the injection volume, rate of infusion, intervertebral foramina, body position, epidural fat, vascular absorption, and the anatomy of a particular species [8][10]. Over the last 10 years, the cranial spread of methylene blue (MB) into the epidural space has been studied in several species [9][13], and a correlation between the volume administered and the cranial distribution of the dye has been observed.…”
Section: Introductionmentioning
confidence: 99%